1999
DOI: 10.2136/sssaj1999.634752x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and Compaction Effects on Soil Water Evaporation and Water and Solute Distributions

Abstract: Water evaporation and solute transport were studied in open soil columns. The study included two different soil materials — Clarinda clay (fine, montmorillonitic, mesic, sloping Typic Argiaquoll) and Fayette silty clay loam (fine‐silty, mixed, mesic Typic Hapludalf) — and three conditions. Two conditions were noncompacted solute‐free and salinized noncompacted soil columns of both Clarinda and Fayette soils, and one condition was compacted salinized soil columns of Clarinda soil only. The initial soil water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…For instance, Shimojimaa et al [1996] reported that in the presence of water table, the evaporation rate from silica sands and glass beads saturated with NaCl solution of ∼0.3 molal (i.e., moles of salt per kilograms of water) was reduced 70% and 30%, respectively, compared to the evaporation rate from pure water. Nassar and Horton [1999]also reported reduction of the evaporation rate due to the presence of KCl in water. Despite the fact that areas such as salt‐affected lands, salt marshes, and salt lakes may contain high salt concentrations, most of the previous evaporation studies focused on the situations in which salt concentrations were relatively low and very few studies attempted to quantify the evaporation process from porous media saturated with highly saline solutions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Shimojimaa et al [1996] reported that in the presence of water table, the evaporation rate from silica sands and glass beads saturated with NaCl solution of ∼0.3 molal (i.e., moles of salt per kilograms of water) was reduced 70% and 30%, respectively, compared to the evaporation rate from pure water. Nassar and Horton [1999]also reported reduction of the evaporation rate due to the presence of KCl in water. Despite the fact that areas such as salt‐affected lands, salt marshes, and salt lakes may contain high salt concentrations, most of the previous evaporation studies focused on the situations in which salt concentrations were relatively low and very few studies attempted to quantify the evaporation process from porous media saturated with highly saline solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The low osmotic potential reduced the vapor pressure in saline soil, which can reduce evaporation. Nassar and Horton (1999) found that evaporation from saline soils varied from 78 to 95% of the evaporation from non-saline soils.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of sustainability, more attentions should also be paid to it since the continuously accumulating salt in the fallow area perhaps has significant effects on soil physical properties and therefore on evaporation during its long run. Experiments show that water transfer is reduced in salinized soils [13][14][15][16] . Numerical simulation shows that the lifetime of a dry drainage system could be a few years before the pores in the top 0.5 mm soil layer are plugged by the precipitated salt and the evaporation stops [9] .…”
Section: Introductionmentioning
confidence: 99%